Hand safety : the irreplaceable tools - Safetycare Australia (Australia : Safetycare Australia Pty. Ltd., 1989)
Presents on the job safety practices to prevent hand injuries from techanical and contact hazards
Accompanied by trainer's manual
VCD format
Keywords: Industrial safety; Accident prevention; Employees; Hands; Wounds and injuries